1984
DOI: 10.1111/j.1600-051x.1984.tb02214.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin induced gingival overgrowth in institutionalized epileptics

Abstract: In a cross-sectional, epidemiological study of phenytoin induced gingival overgrowth in 77 institutionalized persons with epilepsy, the severity of the gum lesions was quantified by means of a precise new technique. Lesion severity was then compared statistically to other clinical and laboratory parameters. Positive correlations were detected between overgrowth severity and gingival inflammation, probing depths, calculus accumulation, plaque score and the measurement gingival margin to mucogingival junction (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 40 publications
1
28
2
Order By: Relevance
“…Our findings are in concordance with previous reports that gingival hypertrophy occurs in -30-50% of dentate patients receiving PHT phenytoin therapy (1,2). The incidence and severity of overgrowth does not depend on PHT dosage, serum concentration, or the patient's age or sex but can resolve if the drug is discontinued or replaced (20). Poor oral hygiene has been shown to be an important determinant of PHT-induced gingival changes (2).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in concordance with previous reports that gingival hypertrophy occurs in -30-50% of dentate patients receiving PHT phenytoin therapy (1,2). The incidence and severity of overgrowth does not depend on PHT dosage, serum concentration, or the patient's age or sex but can resolve if the drug is discontinued or replaced (20). Poor oral hygiene has been shown to be an important determinant of PHT-induced gingival changes (2).…”
Section: Discussionmentioning
confidence: 99%
“…5 It has been suggested that earlier high prevalence figures may be due to a focus on institutionalized and/or hospital neurology out-patient populations. 6 The incidence and severity of overgrowth is greatest on the labial surfaces of the maxillary and mandibular anterior teeth. Figure 3a shows a variation in the clinical appearance of phenytoin-induced gingival overgrowth compared with other va ri ations of drug-induced gi n gi va l overgrowths ( Fig.…”
Section: Gingival Overgrowthmentioning
confidence: 99%
“…[19][20][21]53 A relationship between oral breathing patterns and gingival overgrowth was not observed in the present study, but it has been reported in patients treated with phenytoin. 7,75 It has been shown that nifedipine-induced gingival enlargement may be reduced or prevented by good plaque control, aimed at reducing gingival inflammation, and that in the most severe cases, resective periodontal surgery is used to eliminate excess tissue. [76][77][78][79][80] Also, wherever possible, reducing the drug dose or replacing it with another agent should be considered.…”
Section: Periodontal Evaluation Of Control and Nifedipine-treated Patmentioning
confidence: 99%